Neelkanth Mahadev Temple surrounded by dense vegetation - Temples of India Project Team (Jio Institute, 2024)
The Neelkanth Mahadev Temple is situated amidst dense vegetation, at the foothills, inside the Sariska Tiger Reserve. The temple, built out of sandstone, stands out in the greenery spread across the plains.